What are the needs of people with physical disabilities in the district of Butterworth, and how accessible are available resources to them - Dingana, Carol Joyce Nomalungelo (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScMedSc)--Stellenbosch University, 2012.